Peran Nilai-Nilai Maqashid Syariah dalam Meningkatkan Kualitas Sumber Daya Insani untuk Pembangunan Ekonomi Indonesia - Haanii Haritsa Yuzen; Fanisa Suseno; Indra Saputra; Sandra Dewi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Economic development is determined not only by the availability of natural resources and financial capital, but also by the quality of human resources (HR) as the primary driver of economic activity. In the Indonesian context, the development of HR has become increasingly important in light of the demographic dividend and the rapid growth of the Islamic economy. However, the quality of HR in Indonesia still faces various challenges, such as low productivity, weak integrity, and the suboptimal internalization of Islamic values in the workplace. This study aims to analyze the role of maqashid syariah values in improving the quality of human resources and their contribution to Indonesia’s economic development. This study employs a qualitative approach using library research. Data were obtained through a literature review of books, scientific journals, official reports, and previous studies relevant to maqashid syariah, Islamic economics, and HRD. Data analysis utilized descriptive-qualitative analysis with content analysis as the method. The results of the study indicate that the maqashid al-sharia values—which include hifz al-din, hifz al-nafs, hifz al-‘aql, hifz al-nasl, and hifz al-mal—play a crucial role in shaping competent, ethical, productive, and socially responsible human capital. The implementation of maqashid syariah in education, employment, and Islamic economic institutions can improve the quality of human capital and support equitable and sustainable economic development. This study concludes that the integration of maqashid syariah values into HRD is a vital strategy for realizing Indonesia’s economic development, which is oriented not only toward material growth but also toward the moral and spiritual well-being of society.